2020
DOI: 10.1002/jccs.201900435
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of adenosine triphosphate response to lung cancer epidermal growth factor receptor missense mutations: A molecular insight into “generic” drug resistance mutations

Abstract: Many missense mutations in human epidermal growth factor receptor (EGFR) are clinically involved in lung cancer and may cause acquired resistance to tyrosine kinase inhibitors. Traditionally, the resistance is considered to be established by impairing inhibitor affinity due to the mutations. However, it was found that, instead of blocking inhibitor binding, the gatekeeper mutation T790M can improve the kinase affinity for its natural substrate adenosine triphosphate (ATP), which is thus regarded as a "generic"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The AMP is a nonhydrolyzable analog of ATP; the only difference between them is that the AMP possesses a secondary amine moiety but not an oxygen atom in ATP, which bridges between the first and second phosphates. [20] Therefore, the AMP structure in the complex template could be readily modified to ATP manually (Figure 7).…”
Section: Modeling Egfr Complex With Allosteric Inhibitors and Atp Mol...mentioning
confidence: 99%
See 3 more Smart Citations
“…The AMP is a nonhydrolyzable analog of ATP; the only difference between them is that the AMP possesses a secondary amine moiety but not an oxygen atom in ATP, which bridges between the first and second phosphates. [20] Therefore, the AMP structure in the complex template could be readily modified to ATP manually (Figure 7).…”
Section: Modeling Egfr Complex With Allosteric Inhibitors and Atp Mol...mentioning
confidence: 99%
“…[19] Further study revealed that a number of EGFR missense mutations can considerably or moderately reshape the binding behavior of ATP to EGFR ATP site, thus indirectly influencing the inhibitory capability of ATP-completive inhibitors against EGFR kinase. [20] Here, we first attempted to investigate the molecular effect of the allosteric inhibitor-induced EGFR conformational change on ATP binding. In this procedure, the binding energy changes (ΔΔG ALT ) upon EGFR allostery induced by 11 curated allosteric inhibitors were calculated using molecular mechanics/Poisson-Boltzmann surface area (MM/PBSA) method based on molecular dynamics (MD) production trajectory, which created a ΔΔG ALT profile to visualize ATP response to the binding of 11 allosteric inhibitors to EGFR.…”
Section: Thermodynamic Effects Of Allosteric Inhibitors and Egfr Muta...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, we also observed a modest or moderate activity change (up to 3.8-fold increase) of allosteric inhibitors upon the mutation. This can be explained by two aspects: (i) this mutation is located at the N-terminus of kinase activation loop and can reshape the loop conformation that is involved in the allosteric site, and (ii) the mutation has been reported to influence substrate entry, [22] which would shift the kinase activity and thus alter the kinase-inhibitor interactive behavior. Consequently, all these indirect factors of HER2 C805S mutation come together to modestly or moderately influence the inhibitory activity of allosteric inhibitors.…”
Section: Molecular Mechanism Of Allosteric Inhibitor Response To Her2...mentioning
confidence: 99%